Analysis of PBL-Based Flipbook E-Module in Enhancing Elementary School Students' Critical Thinking Skills: A Literature Study - Endaryati, Sri Adhi; Slamet, St. Y.; Suryandari, Kartika Chrysti (Universitas Muhammadiyah Surakarta, 2023)
Mastery of 21st-century competencies for students is one of the efforts to strengthen the competitiveness of human resources, and one of these competencies is critical thinking skills. Learning tools integrated with technology have become one of the needs of 21st-century students in the digital era. This article is part of research on developing a Problem-Based Learning-based flipbook e-module to enhance critical thinking skills in elementary school students. The article describes one of the results of the needs analysis, which is a literature study consisting of previous research studies related to the use of Problem-Based Learning-based flipbook e-modules in improving critical thinking skills in elementary school students. The research method used in this study is a literature review, specifically analyzing articles from previous research studies on using Problem-Based Learning-based flipbook e-modules to enhance critical thinking skills in elementary school students. The review is limited to accredited journals from 2019 to 2023. The conclusion drawn from this study is that flipbook e-modules have been widely used in elementary school learning, focusing on specific subjects such as Mathematics, Science, and thematic subjects. Flipbook e-modules can be created using Kvsoft Flipbook Maker or Fliphtml5, incorporating elements such as images, videos, music, and quiz exercises. Flipbook e-modules can be effectively used to enhance critical thinking skills when integrated with innovative learning models such as Problem-Based Learning. The findings of this study can serve as a reference for future research and development of e-modules.